PENGARUH TINGKAT SUKU BUNGA, TINGKAT INFLASI, NILAI KURS RUPIAH DAN PRODUK DOMESTIK BRUTO TERHADAP RETURN SAHAM - Wiradharma A, Made Satria; Sudjarni, Luh Komang (E-Jurnal Manajemen; Vol 5 No 6 (2016), 2016)
This study aims to determine the effect of interest rates, inflation rates, rupiah exchange rate and gross domestic product partially onstock return of Food and Beverage companies in Indonesia Stock Exchange from 2009 to 2013. The population in this study is all of the food and beverages sector companies that are listed on the Stock Exchange from 2009-2013 as many as 15 companies. Samples were determined using purposive sampling with criteria include food and beverage company that are listed on the Stock Exchange from 2009-2013 and those company must have the financial data which is related to this research variables in order to obtain sample as many as 11 companies in the food and beverages sector. The data used in this study was obtained from the Indonesian Capital Market Directory from 2009 to 2014. The results showed that the interest rate has significant positive effect on stock returns, inflation rates and the rupiah exchange rate has no effect on stock returns and gross domestic product has significant negative effect on stock returns.
Keywords: (stock return, interest rate, inflation, rupiah exchange value, gross domestic product)